2014
DOI: 10.1007/s10495-014-0995-y
|View full text |Cite
|
Sign up to set email alerts
|

HSP70 desensitizes osteosarcoma cells to baicalein and protects cells from undergoing apoptosis

Abstract: Baicalein is a new drug that has shown promising anti-cancer effects against a broad spectrum of tumors. However, the potential effect on osteosarcoma cells and the mechanisms involved are still largely unknown. Resistance to chemotherapy remains a major obstacle in cancer therapy. Therefore, the aim of the present study was to investigate the anti-tumor effect of baicalein on human osteosarcoma cancer cells and the molecular mechanism involved, as well as identify possible mechanisms of drug resistance. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 35 publications
1
18
1
Order By: Relevance
“…This increased expression of HSP70 is potentially problematic, in that the protein is known to directly suppress the apoptotic cascade and protect cells from doxorubicin-mediated apoptosis in a variety of model systems (Gabai et al 1997(Gabai et al , 1995Karlseder et al 1996;Samali and Cotter 1996). Although we did not confirm a cytoprotective role for the increased HSP70 observed in canine OSA cell lines, induced overexpression of HSP70 in human OSA cell lines partially prevented apoptosis induced by the flavenoid baicalein (Ding et al 2014).…”
Section: Discussioncontrasting
confidence: 61%
“…This increased expression of HSP70 is potentially problematic, in that the protein is known to directly suppress the apoptotic cascade and protect cells from doxorubicin-mediated apoptosis in a variety of model systems (Gabai et al 1997(Gabai et al , 1995Karlseder et al 1996;Samali and Cotter 1996). Although we did not confirm a cytoprotective role for the increased HSP70 observed in canine OSA cell lines, induced overexpression of HSP70 in human OSA cell lines partially prevented apoptosis induced by the flavenoid baicalein (Ding et al 2014).…”
Section: Discussioncontrasting
confidence: 61%
“…HSP70, which is essential for the survival and partial protection of tumor cells from apoptosis, was upregulated after baicalein treatment. This finding suggested that the anti-osteosarcoma property of baicalein can be strengthened in combination with some inhibitors of HSP70 [73]. Broadly speaking, baicalein could be a potential future treatment of patients with osteosarcoma.…”
Section: Baicalein and Osteosarcomamentioning
confidence: 99%
“…Baicalein is a new drug, and baicalein-induced apoptosis in osteosarcoma cells was via a mitochondrial pathway that involved both caspase-dependent and -independent mechanisms. However, baicalein treatment notably upregulated the expression of HSP70, which partially prevented human osteosarcoma cells from undergoing apoptosis, and decreased the sensitivity of osteosarcoma cells to baicalein via the activation of the PI3K/AKT and MAPK/ERK pathways [66]. Celecoxib, a cyclooxygenase-2 inhibitor, induced apoptosis in human osteosarcoma cell line MG-63 via the downregulation of PI3K/Akt, and decreased the level of survival and bcl-2 in cells treated with the combination of celecoxib and cisplatin or wortmannin, a specific PI3K inhibitor [67].…”
Section: Programmed Cell Death In the Treatment Of Osteosarcomamentioning
confidence: 99%